The effect of variation in feedback pattern (teacher assessment/ peer assessment) in the electronic blogs on the development of academic achievement among secondary school students of the computer and information technology curriculum in the province of D - Al - Mutairi, Mohamed Morshed (Journal of Educational and Psychological Sciences, 2019)
The research aimed to identify the effect of variation in feedback pattern (teacher assessment/ peer assessment) in the blogs on the development of academic achievement among secondary school students of the computer and information technology curriculum in the province of Dawadmi. The researcher used the semi-experimental method to answer the research question which depends on the experimental groups and the control group. The study sample consisted of (30) students from the third grade secondary school in Wethilan and Eshairan secondary school. Students were divided among the three groups, the two experimental groups and the control group where each group consists of (10) students. The study revealed a number of results, the most important of them are: The effectiveness of using blogs in developing academic achievement, and the effectiveness of feedback in the blogs on the development of academic achievement, The researcher recommends benefiting from research’s results in encouraging teachers at secondary school in different disciplines to use electronic blogs and services related to feedback and its patterns, focusing on teacher-assessment feedback pattern, and facilitating the role of the teacher as a manager and organizer for educational discussions in and outside the classroom, particularly, in the electronic blogs.
Keywords: blogs; feedback; feedback patterns; feedback pattern teacher evaluation; peer evaluation feedback pattern